Man-Made Rotary Nanomotors: A Review of Recent Development - Kim, Kwanoh (Nanoscale, 2016)
The development rotary nanomotors is an essential step towards intelligent nanomachines and nanorobots. In this article, we review the concept, design, working mechanisms, and applications of the state-of-the-art rotary nanomotors made from synthetic nanoentities. The rotary nanomotors are categorized according to the energy sources employed to drive the rotary motion, including biochemical, optical, magnetic, and electric fields. The unique advantages and limitations for each type of rotary nanomachines are discussed. The advances of rotary nanomotors is pivotal for realizing dream nanomachines for myriad applications including microfluidics, biodiagnosis, nano-surgery, and biosubstance delivery.